2014
DOI: 10.3892/or.2014.3053
|View full text |Cite
|
Sign up to set email alerts
|

Gene profiling and bioinformatics analyses reveal time course differential gene expression in surgically resected colorectal tissues

Abstract: It has previously been reported that gene profiles in surgically-resected colorectal cancer tissues are altered over time possibly due to the different tissue-acquisition methods and sample extraction timing that were used. However, the changes that occur are still not clearly understood. In the present study, time-dependent changes in gene expression profiling in colorectal surgical specimens were analyzed. Normal and tumor tissues at several time-points (0, 30, 60 and 120 min) were extracted, and RNA quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…This indicates the rapid and efficient biomolecule preservation with the PAXgene fixative solution. The similar observation was made previously using another type of fixative RNA Later RNA Stabilization Reagent during collection of resected colorectal tissues: no significant differences in mean RIN scores between the normal and tumour samples were observed 17 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This indicates the rapid and efficient biomolecule preservation with the PAXgene fixative solution. The similar observation was made previously using another type of fixative RNA Later RNA Stabilization Reagent during collection of resected colorectal tissues: no significant differences in mean RIN scores between the normal and tumour samples were observed 17 .…”
Section: Discussionsupporting
confidence: 83%
“…The warm ischemia is the time between surgical incision and tumour specimen removal 12 , which can trigger the cellular stress response 13 14 . Time between tissue removal and its storage, called cold ischemia, should also be minimized because tumour specimen manipulation and storage can both affect the quality of RNA 15 and can distort the gene expression pattern that is associated with a disease condition within minutes 16 17 . For this reason, it is recommended to keep the cold ischemic time short, about 30 minutes maximally 18 .…”
mentioning
confidence: 99%
“…The results of the current study further underline the impact of tissue ischemia time on gene expression. More recently, it has been reported that in colorectal tissue, 10% of genes were differentially regulated 30 to 120 minutes post-resection, but clustering analysis of tumor samples from cases and time points did not reveal a set of similarly regulated genes across all cases [ 23 ] . Within the current study, hierarchical clustering and ANOVA analysis revealed similar changes in gene expression across both normal and tumor samples although gene expression changes were generally lower in tumor compared with normal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…More likely, differences could be due to sample collection. Yamagishi and colleagues extracted all samples including time point zero from post-surgical tissue, but within this study a colonoscopy sample served as a pre-surgical time point [ 23 ] .…”
Section: Discussionmentioning
confidence: 99%